2017
DOI: 10.18203/2394-6040.ijcmph20171318
|View full text |Cite
|
Sign up to set email alerts
|

Case control study for risk factors associated with oral cancer in central India

Abstract: Background: Oral cancer is higher prevalent condition in Asian countries. In India, due to higher proportion of population consuming tobacco in either chewing or smoking and alcohol consumption. Methods: Present matched case control study was carried out in regional cancer institute in central India. The study consists of a total 124 cases and 124 controls. Cases were newly diagnosed patients of oral cancer confirmed by histopathological examination. Results: For cases, the  mean age (years) was 47.62, the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…A male:female ratio of 4.7:1 was observed in this study, which is correlated to previous study. 19 It was observed that the mean duration of the disease was reported as 5.08AE6.46 months which represents the state of delayed diagnosis of OSCC from the onset of the symptoms. Similarly, Naseer et al 20 in their analysis had reported a delay in the diagnosis of OSCC about 4 to 6 months due to the low socioeconomic status of patients and lack of patients availing early medical assistance.…”
Section: Discussionmentioning
confidence: 99%
“…A male:female ratio of 4.7:1 was observed in this study, which is correlated to previous study. 19 It was observed that the mean duration of the disease was reported as 5.08AE6.46 months which represents the state of delayed diagnosis of OSCC from the onset of the symptoms. Similarly, Naseer et al 20 in their analysis had reported a delay in the diagnosis of OSCC about 4 to 6 months due to the low socioeconomic status of patients and lack of patients availing early medical assistance.…”
Section: Discussionmentioning
confidence: 99%